PERFORMANCE OF GROWTH AND YIELD CAYENNE PEPPER (Capsicum frutescens L.) WITH DOSAGE OF NPK AND MONOSODIUM GLUTAMATE (MSG) FERTILIZER - Maryana, Maryana; Sumarwoto, Sumarwoto; Sipangkar, Silvana Delima (Journal TECHNO, 2022)
The demand for cayenne pepper always increases every year along with the increase in population. To increase the yield of cayenne pepper, among others, through fertilization by giving doses of NPK and monosodium glutamate (MSG) fertilizers. The purpose of the study was to determine the best dose of NPK and MSG fertilizer on the growth and yield of cayenne pepper plants. The research was carried out at the Practical Garden of the Faculty of Agriculture, UPN "Veteran" Yogyakarta in August - December 2021. The study used a factorial completely randomized design with 4 replications. The first factor is the dose of NPK fertilizer with levels: NPK fertilizer dose of 1.5 g/plant, and 3.0 g/plant. The second factor with the level: monosodium glutamate dose includes no MSG 0 g/plant; 2.5 g/plant; 5.0 g/plant; and 7.5 g/plant. The results showed that there was no interaction between the dose of NPK fertilizer and monosodium glutamate (MSG) on the growth and yield of cayenne pepper. The dose of NPK fertilizer 3 g/plant and MSG 5 g/plant can provide the best growth and yield of cayenne pepper including number of leaves, number of fruit per plant, total number of fruit per plant and total fruit weight per plant.